Construcción del autoconcepto durante la niñez intermedia y su vínculo con la interacción social - Pineda Narváez, Linda Madelyne; Sánchez Barrera, Nury Paulette (Machala: Universidad Técnica de Machala, 2022)
The self-concept addresses five different dimensions, within these the infant has an image or self-esteem, in order to have an adequate self-concept, for this it is important to know oneself in depth subjectively, having an adequate self-concept will facilitate interaction with other individuals within from various contexts such as, family, school, social and in turn in different situations where the minor will develop their previously acquired skills. This research work on case analysis, aims to determine the construction of self-concept during middle childhood and its link with social interaction. The sample consisted of 10 participants, including 5 mothers and 5 children under nine years of age, the children are in the fourth year of basic education at the Luz de América Basic Education School, located in the City of Machala. Likewise, the present study is based on the cognitive-behavioral epistemological approach, which stands out for explaining the behaviors of the human being from their perception and biopsychosocial environment. The research has a qualitative methodological approach with a hermeneutic phenomenological design with a descriptive scope, because it allows the interpretation of the information collected from the mothers who were interviewed. For the collection of information, the corresponding informed consent was initially submitted to the Educational Unit, later one addressed to the mothers was sent, with the purpose of making it known that the information collected will be solely for academic purposes, by granting us the permission, the beginning was given. To the interviews, two types of instruments were applied, first, the open interview addressed to the mothers, which allowed us to deepen the search for resources according to our objectives focused on the self-concept of their children and the development of their social skills, likewise, A questionnaire with semi-structured questions elaborated by the researchers addressed to the infants was used, which had the purpose of knowing the development of the five dimensions of the self-concept. According to the review of theoretical resources based on the research topic, results were obtained that demonstrated that for the construction of the self-concept it is necessary to address its five dimensions, work/school self-concept, physical self-concept, emotional self-concept, social self-concept, and family self-concept, Regarding the family environment, he responds that for a good social interaction during middle childhood, there must be a healthy self-concept and in turn a good development in his self-esteem, which will allow the minor to face different situations from the resources learned or acquired mainly at home.
El autoconcepto aborda cinco distintas dimensiones, donde el infante tiene una imagen o apreciación propia, para lograr tener un autoconcepto adecuado, es importante conocerse a profundidad de forma subjetiva, el tener un autoconcepto adecuado, facilitará la interacción con otros individuos dentro de diversos contextos como, el familiar, escolar, social y a su vez en distintas situaciones donde el menor desarrollará sus habilidades previamente adquiridas. Este trabajo de investigación sobre análisis de caso, tiene como objetivo determinar la construcción Del autoconcepto durante la niñez intermedia y su vínculo con la interacción social. La muestra estuvo compuesta por 10 participantes, entre ellos 5 madres de familia y 5 menores de nueve años edad, los niños cursan el cuarto año de básica en la Escuela de educación básica Luz de América, ubicada en la Ciudad de Machala. Así mismo el presente estudio se fundamenta en el enfoque epistemológico cognitivo-conductual, que se destaca por explicar las conductas del ser humano desde su percepción y entorno biopsicosocial. La investigación tiene un enfoque metodológico cualitativo con diseño fenomenológico hermenéutico con un alcance descriptivo, debido a que permite la interpretación de la información recopilada de las madres que fueron entrevistadas. Para la recolección de información inicialmente se presentó el consentimiento informado correspondiente hacia la Unidad Educativa, posteriormente se remitió uno dirigido a las madres, con el propósito de dar a conocer que la información recolectada será únicamente con fines académicos, al otorgarnos el permiso se dio inicio a las entrevistas, se aplicaron dos tipos de instrumentos, primero la entrevista abierta dirigida a las madres, que permitió profundizar en la búsqueda de recursos acorde a nuestros objetivos enfocados en el autoconcepto de sus hijos y el desarrollo de sus habilidades sociales, así mismo, se empleó un cuestionario con preguntas semiestructuradas elaborado por los investigadores dirigido a los infantes, el cual tuvo finalidad conocer el desarrollo de las cinco dimensiones de autoconcepto. De acuerdo a la revisión de recursos teóricos basados en tema de investigación, se obtuvo resultados que demuestran que para la construcción del autoconcepto es necesario abordar sus cinco dimensiones, autoconcepto laboral/escolar, autoconcepto físico, autoconcepto emocional, autoconcepto social y, autoconcepto familiar, en cuanto al ambiente familiar, responde que para una buena interacción social durante la infancia intermedia, debe existir un autoconcepto sano y a su vez un buen desarrollo en su autoestima lo que permitirá en el menor afrontar distintas situación desde los recursos aprendidos o adquiridos principalmente en casa.
Keywords: AUTOCONCEPTO; INTERACCION SOCIAL; NIÑEZ INTERMEDIA